The Philosophy of Text Construction in the Literary Discourse of Palestinian Prisoners - daroicha, hussien omr (El Omda in Linguistics and Discourse Analysis, 2022)
Palestinian prisoners have produced a variety of literary genres with distinct artistic and thematic structures. This research examines the philosophy of text construction in the literary discourse of Palestinian prisoners, focusing on creative writing within prisons and highlighting the philosophy of textual formation and its structures in this specific literary context. It also explores this through the interactions of the communicative triad: author, text, and reader. The study clarifies the above using a descriptive methodology, relying on text linguistics and discourse analysis, and then presents a conclusion that includes the research findings and recommendations, along with a bibliography of sources and references.